1984
DOI: 10.1080/10862968409547503
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Importance of Pre-Passage Questions: Effects on Cued Recall

Abstract: This experiment compared the effects of pre-passage questions that quizzed information of different structural importance on college students' cued recall of expository prose passages. Among higher-vocabulary subjects, cued recall of detail information not specifically quizzed by the pre-passage questions was significantly greater in the condition in which pre-passage questions quizzed a detail unit than in the higher-level pre-passage question condition or the no pre-passage question condition, p < .05. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Research in the areas of Ll content learning and reading development has shown that the effective use of pre-reading strategies calls for attention to a wide range of factors, from the level of cognitive development and favoured learning strategies of the target learners (Snow and Lohman, 1984) to the structure of the learning material and the place the target information has in it (Wilhite, 1984). The situation is unlikely to be any simpler in L2 reading, but with the added variable of language proficiency.…”
Section: Resultsmentioning
confidence: 97%
“…Research in the areas of Ll content learning and reading development has shown that the effective use of pre-reading strategies calls for attention to a wide range of factors, from the level of cognitive development and favoured learning strategies of the target learners (Snow and Lohman, 1984) to the structure of the learning material and the place the target information has in it (Wilhite, 1984). The situation is unlikely to be any simpler in L2 reading, but with the added variable of language proficiency.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Wilhite (1982Wilhite ( , 1985 has suggested that postpassage questions (i.e., questions appearing after the passage segment containing the answer) facilitate indirect retention by inducing a cognitive review of the passage that involves either a top-down search of the hierarchical memory representation of the passage or a spread of activation from the passage memory unit directly accessed by the adjunct question. In addition, Wilhite (1983Wilhite ( , 1984 has argued that prepassage questions (i.e., questions appearing before the passage segment containing the answer) facilitate indirect retention by encouraging the encoding of information related to the question and by serving as self-generated retrieval cues at the time of the retention test. With regard to the effects of headings, Brooks et al (1983) have suggested that headings can act as advance organizers by activating schema relevant to the given topic, by encouraging the interrelating of concepts in the text, and by providing cues for subsequent retrieval.…”
mentioning
confidence: 99%
“…However, there are also reasons to believe that the processing induced by the two types of textual aids is not identical. For example, in Wilhite's (1982Wilhite's ( , 1983Wilhite's ( , 1984Wilhite's ( , 1985 research on adjunct questions, he employed verbatim questions that quizzed specific information in the passage, whereas most research on headings (see, for example, Hartley & Trueman, 1983) appears to have employed words or statements intended to indicate the main topic of the following material. Therefore, in situations in which the adjunct questions quiz specific passage information and the headings identify main topics, the organizational effects of headings should be more general than that of the questions.…”
mentioning
confidence: 99%
“…The to-be-remembered passage was a 724-word passage on colour change in leaves used in previous research (e.g. Wilhite, 1982Wilhite, , 1983Wilhite, , 1984. The passage was based on portions of a National Forest Service brochure (USDA, 1967) and was constructed so as to be highly hierarchically organized.…”
Section: Methodsmentioning
confidence: 99%